Research Methods in Communication Disorders - Pring Tim (Whurr Publishers, 2005)
An introductory text for students who are training to be therapists and as an introduction to more advanced methods for clinicians involved in research. Foreword, Preface, Introduction, Designing Experiments, Describing Data, The Normal Distribution and Standarized Tests, Some Statistical Texts, Analysis of Variance, Into the Storm, Analyzing Categorical Data, Correlation and Regression, Measurement, Asking Questions, Observational Research, Efficacy: Are we Going about it in the Right Way?, Single Cases and Specific Therapies, Answers to Exercises, Appendices, References, Index.